The clinical outcome of LMNA missense mutations can be associated with the amount of mutated protein in the nuclear envelope. (26th June 2018) - Al‐Saaidi, Rasha A.; Rasmussen, Torsten B.; Birkler, Rune I.D.; Palmfeldt, Johan; Beqqali, Abdelaziz; Pinto, Yigal M.; Nissen, Peter H.; Baandrup, Ulrik; Mølgaard, Henning; Hey, Thomas M.; Eiskjær, Hans; Bross, Peter; et al.
Abstract : Aims: Lamin A/C mutations are generally believed to be associated with a severe prognosis. The aim of this study was to investigate disease expression in three affected families carrying different LMNA missense mutations. Furthermore, the potential molecular disease mechanisms of the mutations were investigated in fibroblasts obtained from mutation carriers. Methods and results: A LMNA ‐p.Arg216Cys missense mutation was identified in a large family with 36 mutation carriers. Disease expression was unusual with a late onset and a favourable prognosis. Two smaller families with severe disease expression were shown to carry a LMNA ‐p.Arg471Cys and LMNA ‐p.Arg471His mutation, respectively. LMNA gene and protein expression was investigated in eight different mutation carriers by quantitative reverse transcriptase polymerase chain reaction, Western blotting, immunohistochemistry, and protein mass spectrometry. The results showed that all mutation carriers incorporated mutated lamin protein into the nuclear envelope. Interestingly, the ratio of mutated to wild‐type protein was only 30:70 in LMNA ‐p.Arg216Cys carriers with a favourable prognosis while LMNA ‐p.Arg471Cys and LMNA ‐p.Arg471His carriers with a more severe outcome expressed significantly more of the mutated protein by a ratio of 50:50. Conclusion: The clinical findings indicated that some LMNA mutations may be associated with a favourable prognosis and a low risk of sudden death. Protein expression studies suggested that a severe outcome was associated with the expression of high amounts of mutated protein. These findings may prove to be helpful in counselling and risk assessment of LMNA families.